MATHEMATICAL MODELS OF CALCULATION OF THE INGOT THERMOELASTIC CHARACTERISTICS AT MULTISTAGE HEATING - A. N. Chichko; A. S. Borozdin (Литьë и металлургия, 2005)
The method for numerical simulation of thermostressed state of the objects of spatial configuration, moving in multizone temperature field of furnace, is offered. The three-dimensional computer calculations of the moving ingot in terms of different variants of stage heating are carried out.